Advanced flexible automation cell control for aerospace manufacturing. Issue 2 (2nd March 2015) - Webb, Philip; Asif, Seemal; Hogger, Susanne; Kosche, Thomas; Kiernan, Paul
Abstract : Purpose: – This paper aims to describe a new methodology for controlling highly flexible automated manufacturing cells for use in aerospace manufacturing and repair. Design/methodology/approach: – The design methodology and rational of the FLEXA control architecture are described along with it implementation and testing. Findings: – The trials completed so far show that the level of flexibility required can be achieved both at factory, or enterprise level, and at shop floor level. Practical implications: – This work has significant practical implications through its direct applicability for aerospace and other automated manufacturing processes. Originality/value: – The originality of the paper lies in the truly flexible nature of the control system described and its ability to mimic traditional cell control architectures but be expanded through the use of virtual Programmable Logic Controller to control any number of cells without the need for significant extra hardware.